Impact of wall temperature on aerothermal characteristics of an array of surface microstructures - Campanaro, D; He, L (ASME International, 2022)
The aero-thermal behavior of surface microstructures is of wide relevance, especially given the development of additive manufacturing (AM). Of particular interest is the interaction between fluid flow and heat transfer. In this work, two contrasting configurations, a flat plate boundary layer and an array of hemispheric microstructures are examined at three wall-inflow temperature ratios (TR): cooled (TR = 0.5), adiabatic (TR = 1) and heated wall (TR = 1.5). Due to compensation between fluid viscosity and velocity gradient in the boundary layer, the heat transfer effects may appear deceptively small if judged using the common aerothermal parameters (Cf, Nu). The authors find instead the local Reynolds number to be more usefully indicative of such aerothermal interaction. The scale-resolving large eddy simulations (LES) simulations at a range of Reynolds numbers show that the cooled wall case is characterized by a markedly earlier transition which takes place at a much lower (by 50%) bulk flow Reynolds number compared to a near-adiabatic case. Furthermore, it is shown that the incompressible flow LES solutions fail to capture the early transition under the same cooling condition. Finally, a regrouping of the nondimensional parameters (CD, Nu) with TR is proposed leading to a more unified characterization for easier scaling of wall heat transfer effects in practical applications.